Narrative review of endothelial cell metabolism and aberrations in atherosclerosis and peripheral artery disease - Sean M. Carr, PhD; Ottis Scrivner, PhD; Katherine Elizabeth Hekman, MD, PhD (JVS - Vascular Science)
Objective: Several decades of medical research have shown an intricate and definitive connection between dysfunctional endothelium and cardiovascular disorders, including atherosclerosis and peripheral artery disease (PAD). Initial investigations into endothelial cell (EC) physiology highlighted excretion of protein-based growth factors and their signaling pathways with highly specific targets. However, more recent research has focused on nonprotein metabolic signaling. Methods: A narrative review methodology was used. The review involved keyword searches of electronic databases, including Medline and ScienceDirect, conducted in March through October 2022. Review search terms included “endothelial cell metabolism,” “peripheral artery disease metabolism,” “angiogenesis metabolism,” and “endothelial cell metabolic regulation.” The search included primary research articles and subject matter narrative reviews. Abstracts were reviewed for English-language articles published between 2003 and 2022 and supplemented with targeted reference tracing. Results: Small-molecular-weight metabolites have been found to regulate key EC functions such as angiogenesis directly. More specifically, they impact EC behavior through control of energy production, de novo biomass synthesis, redox homeostasis, and production of gases like nitric oxide and hydrogen sulfide. Recent investigations targeting these metabolic pathways have yielded preliminary success in correcting undesirable endothelial dysfunction in atherosclerosis and PAD. Conclusions: Further investigations into therapeutic targeting of EC metabolism may yield novel approaches for treating PAD.